Identifying epilepsy psychiatric comorbidities with machine learning. (22nd January 2020) - Glauser, Tracy; Santel, Daniel; DelBello, Melissa; Faist, Robert; Toon, Tonia; Clark, Peggy; McCourt, Rachel; Wissel, Benjamin; Pestian, John
Abstract : Objective: People with epilepsy are at increased risk for mental health comorbidities. Machine‐learning methods based on spoken language can detect suicidality in adults. This study's purpose was to use spoken words to create machine‐learning classifiers that identify current or lifetime history of comorbid psychiatric conditions in teenagers and young adults with epilepsy. Materials and Methods: Eligible participants were >12 years old with epilepsy. All participants were interviewed using the Mini International Neuropsychiatric Interview (MINI) or the MINI Kid Tracking and asked five open‐ended conversational questions. N‐grams and Linguistic Inquiry and Word Count (LIWC) word categories were used to construct machine learning classification models from language harvested from interviews. Data were analyzed for four individual MINI identified disorders and for three mutually exclusive groups: participants with no psychiatric disorders, participants with non‐suicidal psychiatric disorders, and participants with any degree of suicidality. Performance was measured using areas under the receiver operating characteristic curve (AROCs). Results: Classifiers were constructed from 227 interviews with 122 participants (7 . 5 ± 3 . 1 minutes and 454 ± 299 words). AROCs for models differentiating the non‐overlapping groups and individual disorders ranged 57%‐78% (many with P  < .02). Discussion and Conclusion: Machine‐learning classifiers of spoken language can reliably identify current or lifetime history of suicidality and depression in people with epilepsy. Data suggest identification of anxiety and bipolar disorders may be achieved with larger data sets. Machine‐learning analysis of spoken language can be promising as a useful screening alternative when traditional approaches are unwieldy (eg, telephone calls, primary care offices, school health clinics).